Black Tea Theaflavin Detoxifies Metabolic Toxins in the Intestinal Tract of Mice. Issue 4 (12th January 2021) - Zhang, Shuwei; Ohland, Christina; Jobin, Christian; Sang, Shengmin
Abstract : Scope: This study is to determine the in vivo efficacy of black tea theaflavin (TF) to detoxify two metabolic toxins, ammonia and methylglyoxal (MGO), in mice Methods and results: Under in vitro conditions, TF is able to react with ammonia, MGO, and hydrogen peroxide to produce its aminated, MGO conjugated, and oxidized products, respectively. In TF‐treated mice, the aminated TF, the MGO conjugates of TF and aminated TF, and the oxidized TF are searched using LC‐MS/MS. The results provide the first in vivo evidence that the unabsorbed TF is able to trap ammonia to form the aminated TF; furthermore, both TF and the aminated TF have the capacity to trap MGO to generate the corresponding mono‐MGO conjugates. Moreover, TF is oxidized to dehydrotheaflavin, which underwent further amination in the gut. By exposing TF to germ‐free (GF) mice and conventionalized mice (GF mice colonized with specific‐pathogen‐free microbiota), the gut microbiota is demonstrated to facilitate the amination and MGO conjugation of TF. Conclusion: TF has the capacity to remove the endogenous metabolic toxins through oxidation, amination, and MGO conjugation in the intestinal tract, which can potentially explain why TF still generates in vivo efficacy while showing a poor systematic bioavailability. Abstract : This study reports that black tea theaflavin (TF) has the capacity to remove the endogenous metabolic toxins, such as ammonia and methylglyoxal (MGO), through oxidation, amination, and MGO conjugation in the intestinal tract. By exposing TF to germ‐free mice and conventionalized mice, the gut microbiota is demonstrated to facilitate the amination and MGO conjugation of TF.